Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Petani Padi Sawah Irigasi (Studi Kasus di Kelurahan Biraeng Kecamatan Minasatene Kabupaten Pangkep) - Achmad Zainal Mustaqim Z.; Abd. Asis Pata; Mohammad Anwar Sadat (Universitas Muslim Maros, 2022)
Another problem in agriculture itself concerns the determination of productivity in the agricultural sector, including external factors such as the dry season which hampers agricultural productivity, internal factors are the shrinking of agricultural land due to industrialization and urbanization. The purpose of this study was to determine the factors that affect the income of irrigated rice farming in Biraeng Village, Minasatene District, Pangkep Regency. The data that has been collected is then known to be tabulated to get real data that is used for analysis purposes. This study uses quantitative data and multiple regression to determine the factors that affect the income of irrigated rice farmers in Biraeng Village, Minasatene District, Pangkep Regency. The results of the study can be seen the factors that affect the income of irrigated rice farming in Biraeng Village, Minasatene District, Pangkep Regency, namely rice production, urea fertilizer prices and pesticide prices.